Approaches to Public Integrity - Simona-Roxana Ulman (CES Working Papers, 2015)
Both concepts, integrity and public integrity, are always asked qualities in the social and economic environment, but they are never well defined. In this context, finding precise definitions and offering an ample explanation of the concepts are desired and useful for both economic theoretical and practical levels and become the aim of the present paper. Without a good understanding of a concept, no one is capable to attain it. In this context, it is impossible to ask for a public sector of integrity if both public actors and the citizens do not know what it really means. Therefore, the public actors first have to understand what integrity really supposes, and, then, to be capable to respect its principles. Taking into consideration the effects of public integrity or, on its opposite, of the divergence from it, especially represented by the phenomenon of corruption, on the economy at the macro, but also, on the micro level, public integrity in itself becomes a real economic problem that is aimed to be extensively analyzed through our interdisciplinary approach.
Keywords: Z1; H00; 330; public integrity; public values; public management